2015
DOI: 10.1371/journal.pone.0125072
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of an Alternative Drug to Sulfadoxine-Pyrimethamine as Intermittent Preventive Treatment of Malaria in Pregnancy

Abstract: BackgroundIntermittent preventive treatment in pregnancy (IPTp) with sulfadoxine-pyrimethamine (SP) is recommended in HIV-negative women to avert malaria, while this relies on cotrimoxazole prophylaxis (CTXp) in HIV-positive women. Alternative antimalarials are required in areas where parasite resistance to antifolate drugs is high. The cost-effectiveness of IPTp with alternative drugs is needed to inform policy.MethodsThe cost-effectiveness of 2-dose IPTp-mefloquine (MQ) was compared with IPTp-SP in HIV-negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Overall, 44% of the studies included primigravidas or women who were pregnant for the second time [ 28 , 31 , 32 , 33 , 34 , 35 , 36 , 42 ] and 39% did not specify the number of pregnancies [ 19 , 20 , 29 , 30 , 38 , 39 , 41 ]; one study conducted an economic evaluation of women who had multiple pregnancies [ 37 ] and two included women with HIV [ 40 , 43 ]. Almost all interventions were performed during the second and third trimesters of pregnancy and those that evaluated LBW and infant death continued follow-up until one month after delivery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 44% of the studies included primigravidas or women who were pregnant for the second time [ 28 , 31 , 32 , 33 , 34 , 35 , 36 , 42 ] and 39% did not specify the number of pregnancies [ 19 , 20 , 29 , 30 , 38 , 39 , 41 ]; one study conducted an economic evaluation of women who had multiple pregnancies [ 37 ] and two included women with HIV [ 40 , 43 ]. Almost all interventions were performed during the second and third trimesters of pregnancy and those that evaluated LBW and infant death continued follow-up until one month after delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Added to this is the review which shows that this intervention saves resources for the health provider, patients and their families and constitutes a dominant strategy in the cost-effectiveness plan. Although the IPTp-MQ scheme is also highly cost-effective, low drug tolerance with multiple side effects does not favour its use as a preventive treatment [ 40 ]. Active detection of malaria cases in low endemic regions outside the African continent is recommended [ 58 , 59 , 60 , 61 ]; however, research on the efficacy and cost-effectiveness of this strategy should be improved to lower the complications of PAM in the epidemiological, parasitological and economic aspects as well as in each country's health system coverage.…”
Section: Discussionmentioning
confidence: 99%
“…However, with resistance hampering its use, the prospects for an extended PK evaluation of sulfa drug combinations used for IPTp appear to be limited [ 82 ]. The search for suitable alternative drug (combinations) for IPTp is ongoing [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that two doses of IPTp-SP is a highly cost-effective intervention both in terms of prevention of maternal clinical malaria and reduction in neonatal mortality in this context (Table 2 ). Furthermore, provision of IPTp with a more efficacious drug than SP, even if more expensive, may still remain a cost-effective public health measure to prevent malaria in pregnancy, particularly in HIV-infected pregnant women [ 6 ]. The second cost-effectiveness study was based on the meta-analysis of IPTp with three or more IPTp doses of SP versus two doses across a range of African settings [ 7 ].…”
Section: Purpose Of the Meetingmentioning
confidence: 99%